Penggunaan Media Pembelajaran Berbasis ICT (TikTok) untuk Meningkatkan Kemampuan berbicara di Kelas 8 SMP Miftahul Hidayah - Nidaul Hasanah Ahmad; Agus Gunawan; Muhammad Rizky Fadhil (Akademika, 2023)
People use technology in this digital era in all activities, this can be seen from the development of industry 5.0 which makes it easier for us to access all the information we need. The aim of this research is to investigate the ICT-Based Learning Media (TikTok) to enhance students' speaking skills at SMP Miftahul Hidayah. The design of this research is Classroom Action Research (CAR) and uses qualitative and quantitative data with instruments in the form of interviews, tests, observations and documentation. Participants in this research were 30 students from 8th grade at SMP Miftahul Hidayah. The findings of this research showed that there was an improvement in English-speaking skills in grade 8 of SMP Miftahul Hidayah, as evidenced by data from the pre-test, post-test cycle 1, and post-test cycle 2. The pre-test result showed that the students' mean score was only 63, and the post-test 1 result showed that the students' mean score was 68, and the post-test 2 result showed that the students' mean score was 75, with 87% of the students passing the standard minimum criteria, indicated a significant improvement in teaching speaking by TikTok as a learning media. Based on the findings of the data analysis that teaching English in the classroom using TikTok as a learning media is capable of improving students' speaking skills.